2016
DOI: 10.3345/kjp.2016.59.11.s161
|View full text |Cite
|
Sign up to set email alerts
|

Concurrency of Guillain-Barre syndrome and acute transverse myelitis: a case report and review of literature

Abstract: Guillain-Barré syndrome and acute transverse myelitis manifest as demyelinating diseases of the peripheral and central nervous system. Concurrency of these two disorders is rarely documented in literature. A 4-year-old girl presenting with cough, fever, and an impaired walking ability was admitted to hospital. She had no previous complaints in her medical history. A physical examination revealed lack of muscle strength of the lower extremities and deep tendon reflexes. MRI could not be carried out due to techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Corticosteroid therapy and plasmapheresis are effective for ATM [12]. The first-line therapy for GBS is intravenous immunoglobulins (IVIG) or plasmapheresis while corticosteroids alone have not proven to be beneficial in the management of GBS and may worsen the weakness [5]. If patients of ATM do not show improvement with initial corticosteroid therapy, the next treatment options are plasmapheresis or IVIG [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroid therapy and plasmapheresis are effective for ATM [12]. The first-line therapy for GBS is intravenous immunoglobulins (IVIG) or plasmapheresis while corticosteroids alone have not proven to be beneficial in the management of GBS and may worsen the weakness [5]. If patients of ATM do not show improvement with initial corticosteroid therapy, the next treatment options are plasmapheresis or IVIG [13].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty three cases of overlap syndrome reported so far [4]. These cases were mostly preceded by gastrointestinal infections such as Campylobacter jejuni while other cases were associated with Zika virus, Mycoplasma pneumoniae, Legionella pneumophila, Bartonella henselae, Influenza virus, and Paramyxovirus [5][6][7][8][9][10]. Majority of them were reported in the pediatric population and were commonly associated with acute motor axonal neuropathy [11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on a review of the literature, the majority of reported cases of GBS/TM overlap syndrome have been attributed to infections such as acute viral illness, influenza, Mycoplasma , Legionella , Bartonella and Zika virus 8 11 12. Two previous cases of overlap syndrome after SARS-CoV-2 infection have been reported: one was a paediatric case13 and the other was in a 40-year-old man 14.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, despite early immunomodulatory treatment, severe motor impairment and bladder dysfunction persisted even months after symptom onset. In the few reported cases of concomitant myelopolyradiculitis (22)(23)(24), long-term clinical outcomes varied, although pure motor variants seemed to be associated with a poorer prognosis (25).…”
Section: Discussionmentioning
confidence: 99%